Overlapping features of atopic dermatitis and alopecia areata: from pathogenesis to treatment - Cheng, Jiayi; Jiang, Yugu; Chen, Qianqian; Xiao, Min (Frontiers in Immunology, 2025)
Atopic dermatitis (AD) and alopecia areata (AA) have traditionally been regarded as inflammatory dermatoses with independent pathogenic mechanisms, with the former mostly categorized as a type 2 inflammatory disease and the latter as a type 1 inflammatory disease. However, immunologic studies have shown that the immunologic properties of AD and AA do not strictly follow the traditional classification. Both diseases are associated with systemic Th1, Th2, Th17, and Th22 cytokine imbalances, shared genetic susceptibility loci, overlapping immune pathways, and microbiome-mediated modulation of skin pathology. This review systematically investigates the intricate interactions between AD and AA, focusing on shared pathophysiologic mechanisms such as immune network crosstalk, metabolic dysregulation, and microbial influences. Furthermore, it critically evaluates current therapeutic strategies for overlapping disease manifestations, with a detailed analysis of emerging targeted therapies and their implications for clinical practice. By integrating existing evidence and identifying research gaps, this article aims to provide new perspectives on the understanding of the mechanisms of AD-AA interactions and to inform clinical decision-making and future research directions.